2005
DOI: 10.1002/cncr.21537
|View full text |Cite
|
Sign up to set email alerts
|

Pilot intervention to enhance sexual rehabilitation for couples after treatment for localized prostate carcinoma

Abstract: BACKGROUND The majority of prostate carcinoma survivors experience enduring sexual difficulties and associated distress in the years after definitive treatment. A counseling intervention aimed at improving levels of sexual satisfaction and increasing successful utilization of medical treatment for erectile dysfunction (ED) was developed and pilot‐tested for both the survivor of prostate carcinoma and his partner. METHODS All male participants were 3‐month to 5‐year survivors of localized prostate carcinoma who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
210
2
15

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(235 citation statements)
references
References 42 publications
8
210
2
15
Order By: Relevance
“…This is an important omission as where patient outcomes may not be improved there may be still benefits for partners, which go unseen because they are not assessed. This review exemplifies this as some moderate to strong effects are seen in partners but not patients [38,66]. As discussed previously, the role of partners in patient adjustment can be substantial, which reinforces the need for more consistent assessment of outcomes in partners.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…This is an important omission as where patient outcomes may not be improved there may be still benefits for partners, which go unseen because they are not assessed. This review exemplifies this as some moderate to strong effects are seen in partners but not patients [38,66]. As discussed previously, the role of partners in patient adjustment can be substantial, which reinforces the need for more consistent assessment of outcomes in partners.…”
Section: Discussionmentioning
confidence: 56%
“…Six studies compared the couples intervention with a patient-only intervention [35,36,37,38,39,40], eight studies used a patient-only comparison group and a usual care control group [41,42,43,44,45,46,47,48], one study compared two types of couples interventions with a patient-alone comparison group [49], and the remaining twenty compared a couples intervention with usual care or waiting-list controls. Twenty-eight studies reported effect sizes, or provided information to calculate effect sizes.…”
Section: Main Descriptivesmentioning
confidence: 99%
See 3 more Smart Citations